Leveraging Healthy Volunteers for Anticancer Drug Clinical Pharmacology Studies: A Review Article Featuring Futibatinib as an Example - Aernout D. van Haarst; Sabina Paglialunga; Ziv Machnes; Ikuo Yamamiya; Nanae Hangai; Aram Oganesian (Clinical and Translational Science, 2026)
ABSTRACT Early clinical development of anticancer drugs traditionally focused on exploring candidate treatments in patients. For instance, due to their cytotoxic action, administration of chemotherapies to healthy volunteers (HVs) for evaluation of their pharmacokinetic profiles was not considered feasible nor ethical from a safety and tolerability perspective. With the introduction of more targeted anticancer agents, such as the tyrosine kinase inhibitors (TKIs), enrolment of HVs in clinical pharmacology trials has become an advantageous alternative to early, non‐therapeutic testing in cancer patients. Futibatinib (Lytgobi) is a TKI acting upon the fibroblast growth factor receptor (FGFR) 1–4 and is approved for the treatment of patients with locally advanced or metastatic intrahepatic cholangiocarcinoma harboring FGFR2 gene fusions or other rearrangement. During its clinical development, a series of studies were conducted enrolling HVs, for example, to evaluate pharmacokinetic properties (ADME), drug–drug interaction (DDI) potential and QT liability. In this review article, we will discuss when and why enrolment of HVs can be considered for small molecule anticancer drug trials and touch upon the risks and limitations as well as the advantages of administering this type of drugs to HVs. The case of futibatinib provides an illustrative example of the opportunities and challenges for exploring an anticancer small molecule in HVs.